Obesity Prevalence and Associated Factors in Captive Asian Elephants (Elephas maximus) in China: A Body Condition Assessment Study - Yinpu Tang; Ting Jia; Fangyi Zhou; Liang Wang; Ziluo Chen; Li Zhang (Animals, 2024)
Obesity is a prevalent health issue among captive wildlife, but the obesity status of captive Asian elephants (Elephas maximus) in China has not been systematically investigated. This study assessed obesity in 204 captive Asian elephants across 43 facilities by recording seven potentially relevant variables: sex, age, daily feed supply, proportion of high-calorie feed, outdoor enclosure area, outdoor time, and foot disorders. Body condition was evaluated using visual scoring, revealing a high prevalence of overweight and obesity, particularly in zoo-kept elephants. Over 70% of captive Asian elephants in China were classified as overweight or obese. Statistical analysis indicated that insufficient outdoor time is likely a primary contributor to obesity among zoo elephants. We recommend extending outdoor time and regulating the supply of high-calorie feeds (e.g., fruits, vegetables, and pellets) to promote exercise and balance energy intake. Additionally, implementing positive reinforcement training for routine health checks, including foot exams and blood sampling, could improve data collection on elephant health and welfare, ultimately enhancing obesity management and overall animal well-being.